Predictors of Late‐Onset Atrial Fibrillation Following Isolated Mitral Valve Repairs in Patients With Preserved Ejection Fraction. Issue 8 (15th June 2016) - Magruder, J.Trent; Collica, Sarah; Belmustakov, Stephen; Crawford, Todd C.; Grimm, Joshua C.; Cameron, Duke E.; Baumgartner, William A.; Mandal, Kaushik
Abstract: Background: We sought to determine the incidence of and risk factors for late‐onset atrial fibrillation (LOAF) in patients with preserved ejection fractions undergoing mitral valve repair Methods: We included patients undergoing isolated mitral valve repair (MVR) for degenerative disease between 1997–2014 at our institution with EF ≥60%. Patients who had AF preoperatively were excluded from the final analysis. Our primary outcome, LOAF, was defined as AF occurring after discharge following MVR (≥9 days). Results: 223 patients were included in the study with a mean follow‐up of 4.8 ± 4.6 years. A total of 25 patients developed LOAF, and freedom from LOAF was 93.9% at one year, and 87.3% at five years. Patients developing LOAF were of similar mean age (58 vs. 63 years in controls, p = 0.08) and had similar preoperative comorbidities, but did show a trend toward larger left atrial diameter (5.1 vs. 4.7 cm, p = 0.11). After risk adjustment with Cox regression analysis, only increasing left atrial size was associated with LOAF (HR 1.63, p = 0.04). On follow‐up, 29 patients (10.8%) developed moderate or greater mitral regurgitation at a mean of 2.2 years. Using a mixed‐effects model, we were unable to detect an association between recurrent mitral regurgitation following MVR and LOAF (OR 1.36, p = 0.42). Conclusions: LOAF occurs in about 13% of preserved ejection fraction patients undergoing MVR by five years. Increasing left atrial diameter is an independent predictor of LOAF. Concomitant anti‐arrhythmic procedures may warrant further investigation in patients with preserved ejection fraction and enlarged left atria undergoing MVR. doi: 10.1111/jocs.12774 (J Card Surg 2016;31:486–492)